2001
DOI: 10.1348/014466501163689
|View full text |Cite
|
Sign up to set email alerts
|

Effects of visuospatial tasks on desensitization to emotive memories

Abstract: Objectives: Vivid and intrusive memories of extreme trauma can disrupt a stepwise approach to imaginal exposure. Concurrent tasks that load the visuo-spatial sketchpad (VSSP) of working memory reduce memory vividness during imaginal exposure. Such tasks may help maintain a progressive exposure protocol while minimizing distress during treatment. The current study tested whether relief of distress from a competing VSSP load during emotive imagery is at the cost of impaired desensitization.Design: This study exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

28
155
8
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 182 publications
(195 citation statements)
references
References 44 publications
28
155
8
4
Order By: Relevance
“…On the other hand, non-clinical laboratory studies that investigated the effects of eye movements on autobiographical memories have found decreases in vividness and/or emotionality compared to control conditions such as finger tapping (van den Hout et al 2001), spatial tapping (Andrade et al 1997), and no eye movement (Kavanagh et al 2001;Barrowcliff et al 2004;Gunter & Bodner, 2008). Whilst these laboratory studies show a clear processing effect for eye movements, they did not involve all the procedural elements of EMDR (Shapiro, 1995).…”
mentioning
confidence: 99%
“…On the other hand, non-clinical laboratory studies that investigated the effects of eye movements on autobiographical memories have found decreases in vividness and/or emotionality compared to control conditions such as finger tapping (van den Hout et al 2001), spatial tapping (Andrade et al 1997), and no eye movement (Kavanagh et al 2001;Barrowcliff et al 2004;Gunter & Bodner, 2008). Whilst these laboratory studies show a clear processing effect for eye movements, they did not involve all the procedural elements of EMDR (Shapiro, 1995).…”
mentioning
confidence: 99%
“…Baddeley and Andrade (2000) observed that DVN reduced the vividness with which participants imagined everyday objects and scenes, and Dean, Dewhurst, Morris and Whittaker (2008) showed that DVN interfered with participants' ability to generate images of animals in a mental size comparison task. Clinical applications have shown that DVN reduces the vividness of traumatic images (Kavanagh, Freese, Andrade & May, 2001), as well as the imagery associated with cravings for cigarettes (May, Andrade, Panabokke & Kavanagh, 2010) and food (Kemps, Tiggemann & Christianson, 2008;Kemps, Tiggemann & Hart, 2005;Kemps, Tiggemann, Woods & Soekov, 2004;McClelland, Kemps, Tiggemann, 2006;Steel, Kemps, Tiggemann, 2006).…”
mentioning
confidence: 99%
“…This finding is in agreement with results of research studies focused on impact of eye movements on image vividness and emotional intensity of autobiographic memories. This research indicates that eye movements reduce the vividness and emotional valence of autobiographical memories (Sharpley et al, 1996a;Kavanagh et al, 2001;van den Hout et al, 2001;Barrowcliff et al, 2003Barrowcliff et al, , 2004Lee et al, 2007;Kemps & Tiggemann, 2007;Gunter & Bodner, 2008).…”
Section: Emdr and Working Memorymentioning
confidence: 86%